2012
DOI: 10.1186/1546-0096-10-20
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion-weighted MRI of bone marrow oedema, soft tissue oedema and synovitis in paediatric patients: feasibility and initial experience

Abstract: BackgroundMRI has become the mainstay of diagnostic imaging in paediatric rheumatology for lesion detection, differential diagnosis and therapy surveillance. MR imaging of synovitis, in particular, is indispensable for early diagnosis and follow-up in arthritis patients. We used diffusion-weighted MRI (DWI) as a new imaging modality in comparison to standard MRI sequences to study bone marrow oedema, soft-tissue oedema and synovitis in paediatric patients.MethodsA total of 52 patients (mean age 11 ± 5 years) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 22 publications
5
34
0
1
Order By: Relevance
“…Although the underlying pathophysiological mechanism for these findings is not clarified, several studies observed high synovial signal indicating arthritis in small and large joints [9][10][11][12][13]. Some researchers noted high signal of joint effusion on diffusionweighted scans, which may be attributed to T2 shine-through artefact or to truly increased signal arising from restricted motion of water molecules by macromolecules [12,13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the underlying pathophysiological mechanism for these findings is not clarified, several studies observed high synovial signal indicating arthritis in small and large joints [9][10][11][12][13]. Some researchers noted high signal of joint effusion on diffusionweighted scans, which may be attributed to T2 shine-through artefact or to truly increased signal arising from restricted motion of water molecules by macromolecules [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…The sequences are generally signal-starved, and the synovial layer, even in the presence of active synovitis, rarely exceeds 3 mm in thickness in the knee joint of children and adolescents with juvenile idiopathic arthritis. In contrast, in-plane spatial resolution is practically limited to the range of 1×1 mm 2 to 1.5×1.5 mm 2 [9,12,13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRI is especially sensitive in detecting bone edema during the early stages of inflammation, before bone erosions and/or sclerosis can be detected, and in displaying adjacent inflammatory reactions, e.g. periostitis or synovitis [24]. Although the use of contrast agents can be helpful in the initial assessment of ambiguous bone lesions, nonenhanced sequences may be sufficient for follow-up imaging in CNO patients [23].…”
Section: Sporadic Cnomentioning
confidence: 99%
“…In juvenile idiopathic arthritis (JIA), research into DWI had been conducted in the knee joint [44][45][46][47] and the sacroiliac (SI) joints. 48,49 In the SI joints of patients with enthesis-related arthritis, normalized ADC values (calculated as ADC of the linear ROI over SI joints/by ADC of reference ROI in normal sacral bone) were significantly higher (2.57) than in controls with mechanical lower back pain (1.28).…”
Section: Dwi In Juvenile Idiopathic Arthritismentioning
confidence: 99%